Effect of itraconazole and fluconazole on the pharmacokinetics of valemetostat: An open‐label, phase I study in healthy subjects - Tachibana, Masaya; Matsuki, Shunji; Maekawa, Yutaro; Kuroda, Kana; Shimizu, Takako; Tsutsumi, Junko; Ishizuka, Hitoshi (Clinical and translational science, 2023)
Valemetostat tosylate (valemetostat) is an oral, potent, dual inhibitor of enhancer of zeste homolog (EZH) 2 and EZH1 under investigation for the treatment of cancer, including non‐Hodgkin's lymphomas and solid tumors. Itraconazole and fluconazole are antifungal medications often used as typical inhibitors of cytochrome P450 3A (CYP3A [itraconazole and fluconazole]) and P‐glycoprotein (P‐gp [itraconazole]) in drug–drug interaction studies. Valemetostat is a substrate of CYP3A and P‐gp in vitro. This phase I, open‐label, single‐sequence crossover study (JapicCTI‐183902) assessed the pharmacokinetics (PK) of valemetostat when co‐administered with itraconazole (a strong CYP3A inhibitor and P‐gp inhibitor) or fluconazole (a moderate CYP3A inhibitor) in healthy Japanese male participants 20–45 years of age. Participants were equally allocated to receive two doses of valemetostat 25 mg, once alone and once with either itraconazole or fluconazole (400‐mg induction and 200‐mg once daily maintenance). Valemetostat PK parameters with versus without itraconazole or fluconazole were compared using analysis of variance models. Overall, 32 participants were enrolled. Co‐administration with itraconazole increased valemetostat peak concentration ( C max ) by 2.9‐fold and area under the plasma concentration–time curve extrapolated to infinity (AUC inf ) by 4.2‐fold compared with valemetostat alone. When co‐administered with fluconazole, the C max and AUC inf of valemetostat were each increased by 1.6‐fold. No treatment‐related or grade ≥3 adverse events were reported. Appropriate valemetostat dose reductions are warranted when used concomitantly with strong CYP3A and P‐gp dual inhibitors.